Analisis Faktor – Faktor Yang Mempengaruhi TPAK Dan Kemiskinan Di Provinsi Aceh - Putri Pharaztiwi, Fujiati; Hafifa, Riska; Aldi Syahputra, M.; Asnidar; Ridha, Ahmad (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
This study aims to analyze the influence of education and health on the labor force participation rate and its impact on poverty in Aceh Province in the period 2013-2022. The research method uses a quantitative approach with path analysis. The data in the study came from the Aceh Central Statistics Agency (BPS). The results of the study indicate that education directly has a positive and insignificant effect on the labor force participation rate in Aceh Province, Health has a negative and insignificant effect on the labor force participation rate in Aceh Province, while education, health and labor force participation rates have a negative and insignificant effect on poverty in Aceh Province. Indirectly, education has a negative and insignificant effect on poverty through the labor force participation rate in Aceh Province and health has a negative and insignificant effect on poverty through labor force participation in Aceh Province.